(untitled) (Journal of the Spanish Institute for Strategic Studies, 2023)
On the southern shores of the Baltic Sea, and between the borders of Poland and Lithuania, lies a Russian Oblast of 15,100 square kilometers in area. Its distance from Pskov Oblast, the closest geographical point in Russia, is more than 400 kilometers. This region is a strategic enclave in the rear of the European Union and NATO’s military dominance, which undoubtedly provides a presence as disturbing as it is provocative. In this territory, Russia has deployed numerous units, vehicles and military equipment. The arms build-up on the borders with NATO in recent years has only further reinforced the martial and operational character of this "island" dependent on Moscow. The development and impact of this situation is of great interest for the defense and security dynamics of our environment, as well as the responses to it.